Exploring Language Use Strategies with Zoning-Based Language Rules in SMPIT Hidayatul Qur'an Boarding School - Maulana, Ardi; Aflahah, Noor Aida; Nadia, Hafizhatu; Farhan, Miftah Al; Sari, Ruri Narulita; Amalin, Khusnul (Jurnal Keilmuan dan Keislaman, 2023)
This study aims to describe the implementation of zoning-based language rules in SMPIT Hidayatul Qur’an Boarding School and explore language use strategies implemented by the students. This study is a case study, and the data are collected using interview and observation. The participants are one English teacher and five students with the criteria of having good English score. The results can be concluded in two points, namely: 1) The zoning-based language rules are adapted from Darussalam Gontor Modern Islamic Boarding School. Some zones that are mandatory for formal language are public places such as dormitory, kitchen, mosque, canteen, and school area. However, the use of the formal language in the school area only when outside of school hours. Then, not all students are required to follow this rule because grade 7 students who have just entered SMPIT HQBS need to get used to the rules first. 2) About language use strategies from the students, it is found that they only use retrieval, rehearsal, and communication strategies. They use retrieval strategies to recall their memory of vocabularies, they use rehearsal strategies to practice the use of certain language structures, and they use communication strategies to create meaningful communication through several ways such as through writing, using body language, or mixing formal and informal language. They don’t use coping strategies because they cannot cope with their lack of language knowledge by themselves.